If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + 4x = 42 Solving -7 + 4x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 4x = 42 + 7 Combine like terms: -7 + 7 = 0 0 + 4x = 42 + 7 4x = 42 + 7 Combine like terms: 42 + 7 = 49 4x = 49 Divide each side by '4'. x = 12.25 Simplifying x = 12.25
| 8(x-4)-2=-34 | | 3+8x=3x-2 | | 14+x/3=19 | | (0.3+2x)(0.4+2x)=4.08 | | 3x-8=9x+36 | | 8(5x+1)=2x-6x | | y^2-16y+64+81=0 | | (2/8)x=672 | | -0.848= -0.2(6.5n-2) | | k/-11=0 | | X/8+19=11 | | 7x-3x=4x | | 6w-16=2w | | 3/4x-16=8 | | 12/34=n/96 | | 8c-19=6c+5 | | x+3.8=8.6 | | 17=-7p+38 | | 17s-20=13s | | 3m-11=22 | | 7y-10=5y+6 | | -8(x-1)=-9x | | 8(7b-5)= | | 3x+4=43 | | 3y+3=6y-4y | | x+6+2x-3= | | 2/5(5-a)=2 | | R+5.3=0.4 | | -5d=155 | | -3/4+5/8 | | -18+y=93 | | 6(1+c)=5(c-5) |